Pengelolaan Limbah Rumah Tangga Berpotensi Berbahaya sebagai Instrumen Non-Pidana dalam Hukum Lingkungan - Suci Ridhoandhista; Taufiq Supriadi; Anindita Kusumaedhi; Astari Silmy (Jurnal Hukum Lex Generalis, 2025)
This study examines the application of the precautionary principle as a non-penal instrument in environmental law, focusing on the management of household syringe waste in RT 08 RW 04, Malaka Jaya, East Jakarta. The emergence of syringe waste at the household level, which is normatively classified as hazardous and toxic waste (B3 waste), indicates potential risks to public health and the environment, even though no legal violations or significant pollution impacts have been identified. This research employs a normative juridical approach supported by qualitative-descriptive field observations. The findings reveal that the precautionary principle has been implemented through non-penal mechanisms, including waste segregation at the source, separate collection by the communitybased waste bank and community-based monitoring conducted by neighborhood administrators (RT). However, preventive gaps remain, particularly due to the absence of standardized operational procedures and an integrated management scheme for household medical waste. This study affirms that environmental law functions not only repressively but also preventively through participatory, community-based governance mechanisms.